THE COMMUNICATION STRATEGIES EMPLOYED BY MALE AND FEMALE STUDENTS OF ENGLISH DEPARTMENT OF STAIN GAJAH PUTIH TAKENGON - Susidamaiyanti Susidamaiyanti (Jurnal As-Salam, 2018)
In an educational world, communication is seen as a necessity,as education is a communication process. When communicating, the EFL students often face many obstacles that make them use communication strategies. However, in the same time, theyare required to use the appropriate strategies, as the use of communication strategies contribute to the development of their communicative competence.There are several factors affecting the use of communication strategies by the EFL learners,one of them is gender. Communication between men and women in the classroom is considered as cross-cultural which potentially causes communication breakdown. Pertaining to this problem, this study was conducted to provide answers about the types of communication strategies used by male and female students to overcome their communication problems, and revealing the reasons why they used the strategies. The investigation is based on Bailystock (1990) classification of communication strategies. The study employed a qualitative research design. The subjects were the students who enrolled in Speaking IVcourse of the English Department of STAIN Gajah Putih Takengon. The data were collected through communication tasks (oral presentations), observations, interviews and video recordings. The findings showed that the male and female subjects used L1-based and L2-based communication strategies. Male subjects used mostly the L1-based communication strategies, meanwhile the female subjects dominantly employed the L-2 based communication strategies.The findings also indicated that the male subjects used more L1-based strategiesto help them reaching the communication goal rather than the communicationeffectiveness. In contrast, female subjects dominantly used L2-based strategies to communicate effectively.To sum up, the subjects still used the strategies, which are not beneficial to the development of their communicative competence. Therefore, these findings finally leads to a suggestion thatthe teachers should consider introducing the appropriate communication strategies to make students communicate effectively by incorporating them in the teaching and learning through the classroom activities.